PENGGUNAAN FACEBOOK DALAM ORGANISASI PKK SEBAGAI MEDIA KOMUNIKASI DI DESA TANJUNG TAMBAK BARU KECAMATAN TANJUNG BATU KABUPATEN OGAN ILIR - Dea Eqlima Sari; Isna Wijayani (Journal of Innovation Research and Knowledge, 2025)
This study aims to examine the use of Facebook as a communication medium by the Family Welfare Empowerment (PKK) organization in Tanjung Tambak Baru Village, Tanjung Batu District, Ogan Ilir Regency. The background of the research stems from the phenomenon of the suboptimal use of social media—particularly Facebook—in disseminating information, promoting activities, and strengthening the village's image, despite the village having considerable human and natural resource potential. The study employs a qualitative approach with a case study method, using data collection techniques such as participatory observation, semi-structured interviews, and documentation. The analysis focuses on three main dimensions: (1) the use of Facebook in PKK organizational communication, (2) the effectiveness of Facebook in information dissemination and increasing participation, and (3) the challenges faced in social media management. The findings indicate that Facebook is fairly effective as a medium for interactive communication and broad information outreach, as evidenced by increased community engagement through comments, likes, and content sharing. However, there are obstacles such as limited digital literacy, internet access, and content management continuity. The study recommends strategies to optimize the use of Facebook to expand information outreach, strengthen public participation, and support the achievement of village development goals